The WTO Dispute Settlement System 1995-2006: Some Descriptive Statistics - Henrik Horn; Petros C. Mavroidis (Research Institute of Industrial Economics (IFN), 2008)
The purpose of this paper is to report some initial findings based on the WTO Dispute Settlement Data Set (Ver. 2.0) that the authors have compiled for the World Bank. The data set contains approximately 28 000 observations on the workings of the Dispute Settlement (DS) system. It covers all 351 WTO disputes initiated through the official filing of a Request for Consultations from January 1, 1995, until October 25, 2006, and for these disputes it includes events occurring until December 31, 2006. Each dispute is followed through its legal life via the panel stage, the Appellate Body stage, through to the implementation stage. The descriptive statistics in the paper points to three observations. The first and obvious observation is the almost complete absence of least developed countries. Secondly, less poor developing countries are much more active, and much more successful than the authors would have expected. Third, the EU and the US dominate less than expected, being much more often the subject of complaints, than a complaining party, and they have a very low share of all panellists.
Keywords: F13; F53; O19; 330; WTO; Dispute Settlement; Developing Countries; WTO-Regeln; Internationale Schiedsgerichtsbarkeit; Handelskonflikt; Entwicklungsländer; Welt